PEID (Percutaneous Endoscopic Interlaminar Discectomy): Cautionary Points Based on the Evidence - Jun Ho Lee (Indoscholar, 2018)
Background: Percutaneous endoscopic lumbar discectomy (PELD) is one of the most sophisticated operative procedures for the treatment of lumbar disc herniation (LDH). Endoscopic techniques are now becoming standard in many areas due to expanded technical possibilities of fullendoscopic transforaminal or interlaminar resection of herniated lumbar discs as well as stenosis. However conventional percutaneous endoscopic interlaminar discectomy (PEID) disc operations may sometimes result in subsequent untoward complications due to unnoticed iatrogenic trauma to neural structures, which is mostly related to an anatomical limitation during endoscope insertion. Methods: An appropriate operative indication of the PEID without bone removal or laminectomy can be used to treat LDH cases with an enough interlaminar space (at least ≥ 20 mm by bi-facetal distance) from the reported evidences. Otherwise, there might be several indications for requirement of bone removal; a narrow interlaminar space, disappearance of the concave shape of the upper vertebral laminae, high-grade migration of LDH, recurrent LDH, obesity, or an immobile nerve root. Conclusion: The significance of PEID lies also in its minimal damage to surrounding structures such as muscle, bone, and ligaments. A discrete radiographic evaluation from the patient preoperatively is mandatory before choosing a proper endoscopic surgical modality for the sake of optimal clinical outcome after PEID.